Photobiomodulation therapy enhances topical diclofenac absorption in healthy volunteers – a randomized placebo-controlled trial: preliminary results (Research, Society and Development, 2021)
The inflammatory Muscle-skeletal disorders are responsible for a high economic impact on public health and Pharmacological treatments produce important renal and gastric toxicity especially. However, the real effects of topical NSAID’s still controversial. Photobiomodulation therapy has been used to treat musculo-skeletal conditions.  The aim of this study was to evaluate the effects of Photobiomodulation on topical absorption of sodium diclofenac in healthy volunteers. Methods. The volunteers were selected after an assessment of their state of health. The study began with 12 volunteers with dark skin and 12 white skin. The study was designed to determinate the pharmacokinetic parameters. The volunteers received during hospitalization 5g diclofenac gel in the presence or not of photobiomodulation, following the randomization. A Laser Cluster with 14 laser diodes (100 mW/diode) delivered 3 Joules of Energy/diode (spot area 0.028 Cm2). Blood samples were taken for determination of plasmatic diclofenac concentration (0.5, 1, 2, 3, 4, 5, 6, 7, 8, 10, 12, 14, 16, 18, 24h) by tandem mass spectrometry. Low Power Laser Therapy operating at a wavelength of 650 nm was effective to enhance the absorption of diclofenac emulgel in white-skinned individuals but not in black-skinned individuals. Maximum plasma concentrations were higher in the white-skinned group of volunteers who received low-power laser irradiation prior to drug application when compared to the placebo group.